Early Environmental Conditions Shape Personality Types in a Jumping Spider - Liedtke, Jannis; Redekop, Daniel; Schneider, Jutta M.; Schuett, Wiebke (Frontiers in Ecology and Evolution, 2015)
Individuals of many species across the animal kingdom are found to be less plastic than expected, even in behavioral traits. The existence of consistent behavioral differences between individuals, termed personality differences, is puzzling, since plastic behavior is considered ideal to enable animals to adaptively respond to changes in environmental conditions. In order to elucidate which mechanisms are important for the evolution of personality differences, it is crucial to understand which aspects of the environment are important for the development of personality differences. Here, we tested whether physical or social aspects of the environment during development influence individual differentiation (mean level of behavior) using the jumping spider Marpissa muscosa. Furthermore, we assessed whether those behaviors were repeatable, i.e. whether personalities existed. We applied a split-brood design and raised spider siblings in three different environments: a deprived environment with no enrichment, a socially and a physically enriched environment. We focused on exploratory behavior and repeatedly assessed individual behavior in a novel environment and a novel object test. Results show that the environment during development influenced spiders’ exploratory tendencies: spiders raised in enriched environments tended to be more exploratory. Most investigated behaviors were repeatable (i.e. personalities existed) across all individuals tested, whereas only few behaviors were also repeatable across individuals that had experienced the same environmental condition. Taken together, our results indicate that external stimuli can influence the development of one aspect of personality, the inter-individual variation (mean level of behavior), in a jumping spider. We also found family by environment interactions on behavioral traits potentially suggesting genetic variation in developmental plasticity.